2019
DOI: 10.31083/j.jin.2019.03.183
|View full text |Cite
|
Sign up to set email alerts
|

fNIRS correlates of the development of inhibitory control in young obese subjects

Abstract: Executive functions are closely related to the prefrontal cortex, and inhibitory control is an important component of executive functioning. Previous studies have found that inhibitory control continues to develop after adolescence and that obesity is associated with executive functions. However, few studies have addressed whether obesity affects the development of inhibitory control. Hence, we focused on whether inhibitory control continues to develop after adolescence in obese individuals. We used a Stroop t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Higher parental support can also reduce the negative impact of negative factors on academic achievement. Longitudinal studies have shown that BMI has a negative predictive effect on academic achievement, but girls in the consistently higher BMI group did not experience poor academic achievement when they received parental support ( Huang et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Higher parental support can also reduce the negative impact of negative factors on academic achievement. Longitudinal studies have shown that BMI has a negative predictive effect on academic achievement, but girls in the consistently higher BMI group did not experience poor academic achievement when they received parental support ( Huang et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Papasideri et al reported that age was a significant moderator of the relationship between bilateral medial PFC and general anxiety disorder, and the neural activity over this brain region predicted the anxiety, depression, and negative affect more strongly in older adolescents than in the younger ones ( 89 ). However, age-related differences were less consistent in children with obesity and ADHD ( 23 , 24 , 85 ). For example, Huang et al failed to find an age-related increase in prefrontal cortex activation in obese adolescents (mean age 16.11y ± 4.75y) during a Stroop task ( 85 ).…”
Section: Resultsmentioning
confidence: 92%
“…Gunstad et al (2007) found that the relationship between obesity and executive dysfunction was not associated with age. In contrast, the brain activation measured by functional near-infrared spectroscopy technology (fNIRS) due to Stroop interference did not increase with age in obese subjects (Huang et al, 2019), while activation in normal-weight individuals continued to increase (Adleman et al, 2002). The role of age needs further study.…”
Section: Discussionmentioning
confidence: 91%